2019
DOI: 10.1371/journal.pone.0220827
|View full text |Cite
|
Sign up to set email alerts
|

Genetically regulated gene expression underlies lipid traits in Hispanic cohorts

Abstract: Plasma lipid levels are risk factors for cardiovascular disease, a leading cause of death worldwide. While many studies have been conducted in genetic variation underlying lipid levels, they mainly comprise individuals of European ancestry and thus their transferability to non-European populations is unclear. We performed genome-wide (GWAS) and imputed transcriptome-wide association studies of four lipid traits in the Hispanic Community Health Study/Study of Latinos cohort (HCHS/SoL, n = 11,103), replicated to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 77 publications
0
13
0
Order By: Relevance
“…These results showed that the genetic factor of gene ZNF234 on AD could be potentially mediated through its gene expression, and the expression of this gene could be also potentially involved in the mechanisms of both AD pathology indices of β -amyloid and tangles. Besides AD, gene ZNF234 is also a known risk gene for lipid traits [ 45 ]. The genetically regulated gene expression of this gene might also affect lipid traits, thus leading to a pleiotropy phenomenon of AD and lipid traits [ 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…These results showed that the genetic factor of gene ZNF234 on AD could be potentially mediated through its gene expression, and the expression of this gene could be also potentially involved in the mechanisms of both AD pathology indices of β -amyloid and tangles. Besides AD, gene ZNF234 is also a known risk gene for lipid traits [ 45 ]. The genetically regulated gene expression of this gene might also affect lipid traits, thus leading to a pleiotropy phenomenon of AD and lipid traits [ 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…These results showed that the genetic factor of gene ZNF234 on AD could be potentially mediated through its gene expression, and the expression of this gene could be also potentially involved in the mechanisms of both AD pathology indices of β -amyloid and tangles. Besides AD, gene ZNF234 is also a known risk gene for lipid traits [43]. The genetically regulated gene expression of this gene might also affect lipid traits, thus leading to a pleiotropy phenomenon of AD and lipid traits [44].…”
Section: Resultsmentioning
confidence: 99%
“…is also a known risk gene for lipid traits [43]. The genetically regulated gene expression of this gene might also affect lipid traits, thus leading to a pleiotropy phenomenon of AD and lipid traits [44].…”
Section: Application Studies Of Ad With Individual-level Gwas Datamentioning
confidence: 99%
“…Transcripts whose levels can be confidently imputed from genetic variants are then assessed for phenotype associations [15]. However, like GWAS, TWAS analyses have often included only EA populations [16,17], though some recent efforts have included more diverse populations [18][19][20][21][22]. Furthermore, most reference eQTL datasets used for TWAS include predominantly EA American individuals [23,24], limiting the predictive power of this novel method in other populations with different allele frequencies.…”
Section: Introductionmentioning
confidence: 99%